DIGITAL MARKETING ADOPTION AND THE INFLUENCES TOWARDS BUSINESS SUCCESSES OF MSMEs CREATIVE SECTOR IN INDONESIA AND MALAYSIA - Afifah, Aisyah Nur; Najib, Mukhamad; Sarma, Ma'mun; leong, yee choy (Universitas Brawijaya, Indonesia, 2018)
This research is to identify which factor affecting business success from digital marketing by MSMEs Creative Sector in Indonesia and Malaysia.Data processing and analysis methods in this research are Descriptive Analysis, employing SEM with PLS approach, and quantitative data were mainly investigated. The conclusion of this research are the factor which significantly affects the success of digital marketing uses is knowledge, knowing its benefits can provide more benefits for the future of their businesses.This research is expected to produce knowledge relevant to factors affecting the success of digital marketing benefit towards business success in MSMEs creative sector. The next researcher is expected to examine more respondents and wider research area, and this research is expected to give contribution and references to related institutions.